2010
DOI: 10.1074/jbc.m110.107987
|View full text |Cite
|
Sign up to set email alerts
|

Structural Model for Deoxycytidine Deamination Mechanisms of the HIV-1 Inactivation Enzyme APOBEC3G

Abstract: APOBEC3G (Apo3G) is a single-stranded DNA-dependent deoxycytidine deaminase, which, in the absence of the human immunodeficiency virus (HIV) viral infectivity factor, is encapsulated into HIV virions. Subsequently, Apo3G triggers viral inactivation by processively deaminating C3 U, with 335 polarity, on nascent minus-strand cDNA. Apo3G has a catalytically inactive N-terminal CD1 domain and an active C-terminal CD2 domain. Apo3G exists as monomers, dimers, tetramers, and higher order oligomers whose distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
244
4
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(277 citation statements)
references
References 51 publications
28
244
4
1
Order By: Relevance
“…GST-A3H, GST-A3G, and GST-A3G D128K were expressed and purified as described previously to obtain protein that was cleaved from the GST tag and 95% pure ( Fig. 1) (55).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…GST-A3H, GST-A3G, and GST-A3G D128K were expressed and purified as described previously to obtain protein that was cleaved from the GST tag and 95% pure ( Fig. 1) (55).…”
Section: Methodsmentioning
confidence: 99%
“…2D, fraction 25, 74 kDa) and the Vif HXB2 heterotetramer was a 1:1:1:1 complex (Fig. 2D, fraction 26, 67 kDa) (55,61). The A3G-Vif HXB2 heterotetramer complex resolved in three peak fractions with apparent molecular masses ranging from 157 to 96 kDa (Fig.…”
Section: Interaction Of A3g With Hiv Vif Iiib and Vifmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential consequence of these structural variations is a difference in affinity for DNA binding. Although this affinity still needs to be determined for A3A, the surprisingly high K d (dissociation constant) (Ͼ10 M) of the A3G C terminus for single-stranded DNA (11) suggests that this domain needs to be present at a high concentration close to the target DNA for efficient editing and antiviral activity, as is the case with fulllength A3G in HIV particles (58). The purification of wild-type and mutant A3A and the evaluation of their respective K d s for DNA binding will be required to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this property reflects the asymmetric charge distribution in hA3G, in which the N-terminal domain has a strong positive charge (pI 9.30), while the C-terminal domain is slightly acidic (pI 5.67) (36). It was thus of interest to test mA3 for its polarity, since as noted above its overall domain arrangement is the reverse of that of hA3G and also since (unlike hA3G) both of its domains are positively charged (pIs of the Nand C-terminal domains, 9.15 and 8.74, respectively).…”
Section: Figmentioning
confidence: 99%